IMPLEMENTASI KONSEP GREEN ECONOMY DALAM PENGEMBANGAN WISATA BERWAWASAN LINGKUNGAN PADA PANTAI DATO KABUPATEN MAJENE - , Rezky Ramadhan; Muhammad Sajidin; Riady Ibnu Khaldun; Muhammad Qeyz (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Tourism is an inseparable aspect of people's lives in various parts of the world because it is closely related to economic and social aspects. Tourism must be built on the principle of sustainability, which means that the development is supported by environmental aspects in the long term and must adhere to the principles of justice, morality, and economic benefits for the community. By using the concept of green economy, environmental conditions related to environmental sustainability can be achieved as well as possible. This study was conducted by collecting primary data through direct interviews with participants and conducting field observations. The purpose of the study was to analyze the implementation of the green economy concept in the development of sustainable tourism at the Dato Beach tourist attraction in Majene Regency. The results of this study indicate that Dato Beach has implemented several things included in the green economy concept, including focusing on efficient natural resource management, reducing environmental impacts, and increasing inclusive social welfare.